Management Information System of IMBI Puskesmas, Jayapura Utara District - Sitti Nur Alam; Siti Nurhayati; Preselia Kwando Bonai (IAIC Publishing, 2020)
Imbi Jayapura in carrying out its duties and functions, supported by patient registrationmanagement, management of each poly, pharmacy management, laboratory management, andadministrative management. The recording process in all management is still manual, and patientregistration services can only be done using a prospective patient having to come directly to thePuskesmas, a manual registration process so that it takes a long time to provide health services at thePuskesmas. It is deemed necessary to have a system that can support all management activities. There isno accumulation of patients when registering, faster in service, and accurate in solving patients andreporting problems. This study encourages IMBI puskesmas to serve prospective patients who wish toregister online using the website, carry out medical record management at each clinic, pharmacy andlaboratory quickly and precisely, and carry out the direction of patient reports at Puskesmas Imbi speedilyand accurately. This research resulted in the Puskesmas Imbi Jayapura Management Information Systemused by Puskesmas officers to manage all Puskesmas activities.